The role of scapular dyskinesis on rotator cuff tears: a review of the current knowledge - Diana Cabral Teixeira (2021)
Scapular dyskinesis can be present in healthy individuals as in patients with shoulder pathology. It is no consensual if the altered patterns of scapular kinematics cause or exacerbate rotator cuff tears pathology. Regardless of being the cause or the consequence of rotator cuff tear, scapular dyskinesis impairs shoulder function, worsens the symptoms, and compromises the clinical intervention success. The first recommended treatment for rotator cuff tears is the physical therapy, and it should address scapular dyskinesis whenever it is present. Surgery is reserved for non-responsive cases. Post-surgical physical therapy protocols after rotator cuff repair must consider scapular dyskinesia to improve the outcomes.